(untitled) (Journal of Health Sciences, 2021)
Introduction: Breakthrough technologies in the neonatal intensive care unit (NICU) revolutionized neonates’ quality of care. Mother scented simulated hand (MSSH) is an ergonomically designed supportive hand that uses the power of touch to simulate the feeling of being held and cuddled. This study aimed to determine the effect of MSSH on promoting comfort among mechanically ventilated preterm neonates during invasive procedures.Methods: A quasi-experimental, pre-posttest two groups study was carried out in NICU in Smouha, Alexandria. A sample of 62 mechanically ventilated neonates was randomly assigned to two equal groups; the study group wrapped with a warm MSSH during the invasive procedures while the control group received standard care of NICU. Two observers independently rated the neonates’ level of comfort, distress, and pain during endotracheal suctioning (ETS) and heel prick using COMFORTneo scale.Results: It is revealed that the mechanically ventilated neonates had a significantly higher comfort level with MSSH than the standard care during and after both ETS and heal break (p < 0.001 for each). The neonates had significantly lower distress and pain scores when encircled by MSSH during invasive procedures than standard care (p < 0.001 for NRS distress and p < 0.001 for NRS distress).Conclusion: Wrapping the preterm neonates with a warm MSSH promotes comfort and reduces their pain and distress during invasive procedures, especially when their mothers are not physically available.